Automation of Library and Information Centres With Open Source Software - Desai, Ramkrishna G (Journal of Advanced Research in Library and Information Science, 2021)
This article is describing use of automation with open sources of water in library. The library is an ever-growing centre is construction of the present library is not going to be completed in the future. This paper shows that automation and open source software should be used in the library for all the library materials which are difficult to maintain. The benefits of automation and the use of open source software are also explained in this paper. Major librariesare use KOHA open access to tware in library. How to cite this article:  Desai RG. Automation of Library and Information Centres With Open Source Software. J Adv Res Lib Inform Sci 2021; 8(2): 10-12.